Evaluation of Purkait's triangle method as an alternative method of sex estimation from proximal femora in a Thai population - Tawachai Monum (2018)
© 2018 Japan Health Sciences University & Japan International Cultural Exchange Foundation. Objective: In 2005, Purkait reported a high percentage of accuracy of a sex estimation method which used the traction epiphysis of proximal femur. However, this method was explored in many populations and the results differed and were not consistent. The aim of this study is to evaluate Purkait's method in a Thai population. Design: A metric for the proximal femur to estimate sex. Materials and Methods: The femora of 90 Thai males and 90 females were investigated using the Purkait method. The advocated triangle of the proximal femur was measured on the posterior aspect in each case. The points of the triangle were termed A, B and C and measurements were made between the points. Point A was defined as the most laterally dipping point of the articular surface of the femoral head, while point B was defined as the most medial projection of the greater trochanter and the highest point of the lesser trochanter was defined as C. Results: The lengths of all variables (AB, AC and BC) were smaller than these reported in previous studies. BC was the best variable to estimate the sex while AB was not significant between sexes. However, the percentage of accuracy of BC is still only 73.9 and if the measurements BC and AC are combined the accuracy only increases to 74.4%. Conclusion: This result was lower than that reported by previous studies and the technique should be applied with caution to the Thai population. However it could be of some use in sex determination in cases where the remains involve fragmentation of the femora.